Role of the AlGaN barrier on the long-term gate reliability of power HEMTs with p-GaN gate. (November 2020) - Tallarico, A.N.; Posthuma, N.E.; Bakeroot, B.; Decoutere, S.; Sangiorgi, E.; Fiegna, C.
Abstract: Forward gate constant voltage stress (CVS) has been performed on GaN-on-Si (200 mm) HEMTs with p-GaN gate, controlled by a Schottky metal-retracted/p-GaN junction, processed by imec with different gate process splits. In particular, the adoption of devices with a different magnesium (Mg) concentration in the p-GaN layer, AlGaN barrier thickness and AlGaN aluminium percentage (Al%), allowed us to identify the degradation of the AlGaN barrier as responsible for time-dependent gate breakdown at room temperature. Lowering the Al% of the barrier and the Mg concentration of the p-GaN layer leads to a longer gate lifetime, while an optimum AlGaN barrier thickness is identified at given Al%.